Alcohol, Cannabis, and Opioid Use Disorders, and Disease Burden in an Integrated Health Care System. Issue 1 (January 2017) - Bahorik, Amber L.; Satre, Derek D.; Kline-Simon, Andrea H.; Weisner, Constance M.; Campbell, Cynthia I.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: We examined prevalence of major medical conditions and extent of disease burden among patients with and without substance use disorders (SUDs) in an integrated health care system serving 3.8 million members. Methods: Medical conditions and SUDs were extracted from electronic health records in 2010. Patients with SUDs (n = 45, 461; alcohol, amphetamine, barbiturate, cocaine, hallucinogen, and opioid) and demographically matched patients without SUDs (n = 45, 461) were compared on the prevalence of 19 major medical conditions. Disease burden was measured as a function of 10-year mortality risk using the Charlson Comorbidity Index. P -values were adjusted using Hochberg's correction for multiple-inference testing within each medical condition category. Results: The most frequently diagnosed SUDs in 2010 were alcohol (57.6%), cannabis (14.9%), and opioid (12.9%). Patients with these SUDs had higher prevalence of major medical conditions than non-SUD patients (alcohol use disorders, 85.3% vs 55.3%; cannabis use disorders, 41.9% vs 23.0%; and opioid use disorders, 44.9% vs 26.1%; all P < 0.001). Patients with these SUDs also had higher disease burden than non-SUD patients; patients with opioid use disorders ( M = 0.48; SE = 1.46) had particularly high disease burden ( M = 0.23; SE = 0.09; P < 0.001). Conclusions: Common SUDs, particularly opioid use disorders, are associated with substantial disease burden for privately insured individuals without significant impediments to care. This signals the need to explore the full impact SUDs have on the course and outcome of prevalent conditions and initiate enhanced service engagement strategies to improve disease burden.